Association between stressful life events and grey matter volume in the medial prefrontal cortex: A 2‐year longitudinal study. Issue 11 (12th April 2022) - Ringwald, Kai G.; Pfarr, Julia‐Katharina; Stein, Frederike; Brosch, Katharina; Meller, Tina; Thomas‐Odenthal, Florian; Meinert, Susanne; Waltemate, Lena; Breuer, Fabian; Winter, Alexandra; Lemke, Hannah; Grotegerd, Dominik; et al.
Abstract: Stressful life events (SLEs) in adulthood are a risk factor for various disorders such as depression, cancer or infections. Part of this risk is mediated through pathways altering brain physiology and structure. There is a lack of longitudinal studies examining associations between SLEs and brain structural changes. High‐resolution structural magnetic resonance imaging data of 212 healthy subjects were acquired at baseline and after 2 years. Voxel‐based morphometry was used to identify associations between SLEs using the Life Events Questionnaire and grey matter volume (GMV) changes during the 2‐year period in an ROI approach. Furthermore, we assessed adverse childhood experiences as a possible moderator of SLEs‐GMV change associations. SLEs were negatively associated with GMV changes in the left medial prefrontal cortex. This association was stronger when subjects had experienced adverse childhood experiences. The medial prefrontal cortex has previously been associated with stress‐related disorders. The present findings represent a potential neural basis of the diathesis‐stress model of various disorders.